2010
DOI: 10.1093/ejechocard/jeq047
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an echo-Doppler decision model to predict left ventricular filling pressure in patients with heart failure independently of ejection fraction

Abstract: This sequential testing is useful to non-invasively predict LVFP in patients with LV dysfunction, especially in those with preserved EF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 26 publications
4
32
0
Order By: Relevance
“…Recently, several reports have suggested that combinations of two or more parameters might be superior to the utilization of only a single parameter in predicting LVFP elevation or in establishing diastolic dysfunction in patients with a normal LVEF . In these studies, parameter combinations included either exclusively echocardiographic variables or combinations of natriuretic peptides with echocardiographic Doppler variables . However, only one of these studies was implemented during exercise .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have suggested that combinations of two or more parameters might be superior to the utilization of only a single parameter in predicting LVFP elevation or in establishing diastolic dysfunction in patients with a normal LVEF . In these studies, parameter combinations included either exclusively echocardiographic variables or combinations of natriuretic peptides with echocardiographic Doppler variables . However, only one of these studies was implemented during exercise .…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that standalone assessment of e-PADP could reliably identify most patients with elevated PAWP ( Table 2 and Figures 1 and S4A), because of its high positive predictive value ( Table 2). Its accuracy was superior to that of standalone E/e'm, that is currently the most widely used single variable to assess LVFP [12][13][14][15] (Table S6), as it is evident from the wide scatter pattern in the relationship between E/e'm and PAWP ( Figure S3A). A recent meta-analysis did not support the use of E/e'm in patients with preserved EF.…”
Section: Advantages Of the Algorithm Approachmentioning
confidence: 99%
“…36 A number of indices have been used to achieve accurate assessment of filling pressures including LV pulsed-wave filling velocities (E/A ratio, E-wave deceleration time), pulmonary venous flow (ratio of systolic wave velocity and diastolic wave velocity and the difference in duration between pulmonary venous flow and mitral flow at atrial contraction), tissue Doppler imaging and left atrial volume index (Table 1). 37,38 Particularly, an E-wave deceleration time <150 ms has been found to be highly predictive of a PCWP >15 mmHg. 39 The restrictive transmitral flow pattern (reduced E-wave deceleration time below 150 ms) has been shown to be an important predictor of cardiac morbidity and mortality in patients with systolic HF.…”
Section: The Potential Role Of Echocardiographic Biomarkers In Hearmentioning
confidence: 99%